Estudo comparativo dos efeitos dos complexos de inclusão de Clorexidina em ciclodextrinas em células bacterianas e eucariotas. - Karina Imaculada Rosa Teixeira (2012)
The current study was designed to assess the ability of chlorhexidine (CX): cyclodextrins (Cd) complexes to target specifically the eukaryotic and prokaryotic membrane. To further explore the influence of the addition of £\-Cd, £]-Cd and Hp-£]-Cd of the complexes in the specificity, invitro studies were conducted increasing cyclodextrin molar rate against oral pathogens and the solubilization of ergosterol was also investigated. The particles measurement and zeta potential were evaluate by by photon correlation spectroscopy and laser Doppler anemometry using aZetasizer 3000 HS. The resulting nanoparticles were in the size range of 265¡V1451 nm and showed a zeta potential ranging from -2 to +18 mV. The association of these compounds led to an variable increase of the size of the nanoparticles (493¡V1451 nm), with significantmodification of their zeta potentials. The antimicrobial activity of the complexes showed that CX:£\-Cd complex was more efficient to inhibit C.a; CX:£]-Cd for A.a and CX:Hp-£]-Cd for S.m. The ergosterol solubilization analysis revealed highest values with 1:3 and 1:4 £\-Cd complexes. The viability assays of different cells were used to assess in vitro cytotoxicity. The inclusion complexes also decreased selectively the cytotoxicity of CX been Ò- and Hp-£]-Cd less cytotoxic in a dose dependent manner in fibroblast than Ñ-Cd, whereas Hp-£]-Cd inclusion complexes had no effect to high cytotoxic effects on Caco-2 cells in a dose-dependent. To study the effects of these compounds in the calcium metabolism was performed an alkaline phosphates assay.Supramolecular complexes inhibited alkaline phosphatase delivery at 0.1%. Ò- and Hp-Ò-Cd increase the alkaline phosphatase delivery at 0.001%. In general the Ñ-, Ò- and Hp-Ò-Cd increase the CX antimicrobial activity and has specific-cells effect. The effects ofsupramolecular complex in the cellular cytoskelet and Calcium transient levels were studied by confocal immunofluorescense microscopy. The results show dramatic alterations in the both parameters for chlorhexidine control. The alterations caused by supramolecular complexes treatment decreasing in 1:3 and 1:4 molar ratio. Hp-£]-Cd showed the biggest concentration of calcium in the cells. Cyclodextrin provide a unique tool to modulate cellular cholesterol in membranes and cytotoxicity, this characteristic could be used for designed different formulations with cyclodextrin favoring a selective activity.The inclusion of chlorhexidine in cyclodextrin enhanced this antimicrobial effect and attenuated the cytotoxic effects.